Impacts of quaker beans over sensory characteristics and volatile composition of specialty natural coffees. (16th April 2021) - Rabelo, Mariane Helena Sances; Borém, Flávio Meira; Lima, Renato Ribeiro de; Alves, Ana Paula de Carvalho; Pinheiro, Ana Carla Marques; Ribeiro, Diego Egídio; Santos, Cláudia Mendes dos; Pereira, Rosemary Gualberto Fonseca Alvarenga
Highlights: The threshold of sensory perception for the presence of Quaker is higher than 10%. The flavor of Quaker beans present in the beverage was described as an "immature fruit". Quaker has a volatile composition formed from precursors present in immature beans. Abstract: The objective of this study was to evaluate the volatile composition and the sensory effect of the presence of Quaker beans in natural specialty coffee beverage and, consequently, to confront the requirement of the Specialty Coffee Association regarding the total absence of Quaker beans in a natural specialty coffee batch. Sensory analysis and volatile composition were performed for three different colorations of Quaker beans, added separately to natural specialty coffee samples at seven different concentrations. Beans with color equal to or above Agtron 82.8 negatively affected the sensory characteristics of natural specialty coffee only from the presence of 7 Quaker beans in one cup (65 beans). Through the analysis of volatile composition, volatile compounds formed during roasting were identified in Quaker beans from precursors present in raw immature beans. Therefore, the color and sensory characteristics of Quaker are a consequence of the chemical composition of an immature bean.